PENDATAAN ASET WAKAF MUHAMMADIYAH: TINJAUAN AKUNTANSI SYARIAH - Yusuf, Muhammad Zulfikar; Satibi, Ibi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
This study aims to describe the benefits of data collection on the SIMAM application owned by Muhammadiyah. This research uses descriptive qualitative research with unstructured interview. This research was conducted at the Muhammadiyah Central Executive Board of Waqf and Property, with the research object being the Muhammadiyah Asset Management Information System (SIMAM) application. Based on the analysis results obtained, it was found that the data collection carried out by Muhammadiyah in the application of the Muhammadiyah Asset Management Information System (SIMAM) based on sharia accounting principles was able to optimize and utilize assets owned by Muhammadiyah as part of maqoshid sharia.